Comparative Study on Hatha Yoga Vs Conventional Physiotherapy Management in Pain and Functional Outcome in Osteoarthritis Knee Subjects. - S., Joyce Angel; Kotteeswaran, K. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Osteoarthritis is a degenerative condition of the joints that frequently impacts the knee. OA can cause discomfort, stiffness, swelling, instability of joint and decreased muscle strength which limits the movement and lowers the quality of life. Hence the study is to determine the effects of Hatha Yoga VS Conventional Physiotherapy Management in pain and functional outcome in Osteoarthritis Knee Subjects. Purpose: The purpose of the study is to compare Hatha Yoga VS Conventional Physiotherapy Management in pain and functional outcome in osteoarthritis knee subjects. Materials and Methods: About 196 subjects were selected from Vijay Physiotherapy Clinic by using KOOS based on inclusion and exclusion criteria. Experimental protocol and procedures were informed to all the subjects before giving their informed consent. Subjects were allocated into 2 groups. Hatha yoga group and Conventional group, each had 98 subjects. Hatha yoga group performed Hatha yoga and Conventional group performed Conventional Physiotherapy Management for a duration of 45 minutes, 4 days per week with IFT for 10 minutes. These interventions were given for 4 weeks. Study period: October 2022 to July 2023. Result: The Pre-test and Post-test values were analyzed results suggest that Hatha Yoga group has significant improvement when compared with Conventional group with P value<0.0001. Conclusion: According to this study, Hatha yoga group had better results than conventional group, Hatha yoga is more effective in reducing pain and improving functional outcome among osteoarthritis knee subjects.